The Diagnostic Role of 18F-Choline, 18F-Fluciclovine and 18F-PSMA PET/CT in the Detection of Prostate Cancer With Biochemical Recurrence: A Meta-Analysis - Wang, Rang; Shen, Guohua; Huang, Mingxing; Tian, Rong (Frontiers in Oncology, 2021)
Background: Diagnosing the biochemical recurrence (BCR) of prostate cancer (PCa) is a clinical challenge, and early detection of BCR can help patients receive optimal treatment. We conducted a meta-analysis to define the diagnostic accuracy of PET/CT using 18F-labeled choline, fluciclovine and prostate-specific membrane antigen (PSMA) in patients with BCR. Methods: Multiple databases were searched until March 30, 2021. We included studies investigating the diagnostic accuracy of 18F-choline, 18F-fluciclovine and 18F-PSMA PET/CT in patients with BCR. The pooled sensitivity, specificity and detection rate of 18F-labeled tracers were calculated with a random-effects model. Results: A total of 46 studies met the included criteria; 17, 16 and 13 studies focused on 18F-choline, fluciclovine and PSMA, respectively. The pooled sensitivities of 18F-choline and 18F-fluciclovine were 0.93 (95% CI, 0.85–0.98) and 0.80 (95% CI, 0.65–0.897), and the specificities were 0.91 (95% CI, 0.73–0.97) and 0.66 (95% CI, 0.50–0.79), respectively. The pooled detection rates of 18F-labelled choline, fluciclovine and PSMA were 66%, 74% and 83%, respectively. Moreover, the detection rates of 18F-labelled choline, fluciclovine and PSMA were 35%, 23% and 58% for a PSA level less than 0.5 ng/mL; 41%, 46% and 75% for a PSA level of 0.5-0.99 ng/mL; 62%, 57% and 86% for a PSA level of 1.0-1.99 ng/mL; 80%, 92% and 94% for a PSA level more than 2.0 ng/mL. Conclusion: These three 18F-labeled tracers are promising for detecting BCR in prostate cancer patients, with 18F-choline showing superior diagnostic accuracy. In addition, the much higher detection rates of 18F-PSMA showed its superiority over other tracers, particularly in low PSA levels.